Cribriform neuroepithelial tumor: molecular characterization of a SMARCB1‐deficient non‐rhabdoid tumor with favorable long‐term outcome. (11th August 2016) - Johann, Pascal D.; Hovestadt, Volker; Thomas, Christian; Jeibmann, Astrid; Heß, Katharina; Bens, Susanne; Oyen, Florian; Hawkins, Cynthia; Pierson, Christopher R.; Aldape, Kenneth; Kim, Sang‐Pyo; Widing, Eva; et al.
Abstract: Rhabdoid phenotype and loss of SMARCB1 expression in a brain tumor are characteristic features of atypical teratoid/rhabdoid tumors (ATRT). Rare non‐rhabdoid brain tumors showing cribriform growth pattern and SMARCB1 loss have been designated cribriform neuroepithelial tumor (CRINET). Small case series suggest that CRINETs may have a relatively favorable prognosis. However, the long‐term outcome is unclear and it remains uncertain whether CRINET represents a distinct entity or a variant of ATRT. Therefore, 10 CRINETs were clinically and molecularly characterized and compared with 10 ATRTs of each of three recently described molecular subgroups (i.e. ATRT‐TYR, ATRT‐SHH and ATRT‐MYC) using Illumina Infinium HumanMethylation450 arrays, FISH, MLPA, and sequencing. Furthermore, outcome was compared to a larger cohort of 27 children with ATRT‐TYR. Median age of the 6 boys and 4 girls harboring a CRINET was 20 months. On histopathological examination, all CRINETs demonstrated a cribriform growth pattern and distinct tyrosinase staining. On unsupervised cluster analysis of methylation data, all CRINETs examined exclusively clustered within the ATRT‐TYR molecular subgroup. As ATRT‐TYR, CRINETs mainly showed large heterozygous 22q deletions (9/10) and SMARCB1 mutations of the other allele. In two patients, SMARCB1 mutations were also present in the germline. Estimated mean overall survival in patients with CRINETs was 125 months (95% confidence interval 100–151 months) as compared to only 53 (33–74) months in patients with ATRTs of the ATRT‐TYR subgroup (Log‐Rank P < 0.05). In conclusion, CRINET represents a SMARCB1‐deficient non‐rhabdoid tumor, which shares molecular similarities with the ATRT‐TYR subgroup but has distinct histopathological features and favorable long‐term outcome.